Implementation of Wizer.me Based E-LKPD for Science Learning on Digital Literacy Activities in Elementary School - Ade Eka Anggraini; Mardhatilah; Khusnul Khotimah; Irene Milenia Siki; Oriza Zativalen; Mohammad Yusuf Randy; Enio Mohd Sufian Kang (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to develop and implement an interactive electronic Learner Worksheet (E-LKPD) utilizing the Wizer.me application for science education, specifically targeting digital literacy activities in elementary schools. It also aims to evaluate the effectiveness of this E-LKPD in enhancing the critical thinking skills of sixth-grade students. The research adopts a Research and Development (R&D) approach employing the ADDIE model, encompassing the phases of analysis, design, development, implementation, and evaluation. The study involved 27 sixth-grade students and 2 teachers from a public elementary school located in Malang City. Validation by material experts resulted in a total score of 37 out of 45, translating to 82%, which falls into the very high category. Meanwhile, media expert validation yielded a total score of 55 out of 70, corresponding to 79% in the high category. The trial results, along with student feedback, indicated that the E-LKPD is highly feasible for use and significantly enhances student engagement and comprehension through interactive features such as illustrated quizzes and explanatory videos. An analysis of pretest and post-test data demonstrated a notable improvement in students' critical thinking skills regarding Outer Space Object material, with an average score increase of 22.19%. These findings indicate that the Wizer.me-based E-LKPD serves as an effective interactive learning medium, supporting science education and reinforcing digital literacy in elementary schools.